العنف المنزلي في مسرحية لعنة الطبقة الجائعة للكاتب سام شيبارد - عمران ممدوح (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper attempts to examine family relationships in Sam Shepard’s Curse of the Starving Class, focusing on the violence, both verbal and physical, that governs those relationships. Attention is paid to the causes and manifestations of the violent relationship between Weston and his wife Ella as well as to its effect on their children Wesley and Emma. In the process, the paper foregrounds the wider historical context of domestic violence as well as Shepard’s skillful use of memorable visual images and narrative episodes in illustration of aggression within the family. يحاول هذا البحث دراسة العلاقات الأسرية في مسرحية لعنة الطبقة الجائعة للكاتب الأمريكي سام شيبارد مركزاً على العنف، بشقيه الجسدي واللفظي، الذي يحكّم هذه العلاقات. وفي هذا الصدد، يركز البحث على أسباب العلاقات العنيفة ومظاهرها بين ويستون وزوجته إيلا، ويُوضح أثر تلك العلاقة العنيفة في وليديهما ويسلي وإيما. وفي أثناء ذلك، يُظهر البحث مهارة شيبارد في استخدامه لصور مرئية وقصص رائعة تجسيداً لتلك العلاقة العنيفة ضمن العائلة، كما يضع تلك العلاقة في سياقها التاريخي.